2011
DOI: 10.1080/09712119.2011.558612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginger root (Zingiber officinale) on egg yolk cholesterol, antioxidant status and performance of laying hens

Abstract: To investigate the effect of ginger root powder on egg production, cholesterol, antioxidant and hen performance, 100 30-week-old laying hens (Hy-Line W36) were equally and randomly assigned to four diets for 8 weeks. The diets included a control diet (0.0% ginger) and diets with 0.25, 0.5 or 0.75% ginger root powder. Although, the egg weight, feed intake and feed conversion ratio were not (PB0.05) influenced by ginger root supplementation, the egg production was higher and cholesterol lower (PB0.05) in birds f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 9 publications
5
26
0
1
Order By: Relevance
“…Similar results were found by Akbarian et al. () who reported that the dietary addition of ginger (0.25%, 0.5% and 0.75%) reduced egg cholesterol levels without any adverse effect on egg weight or feed conversation ratios.…”
Section: Results and Diccussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were found by Akbarian et al. () who reported that the dietary addition of ginger (0.25%, 0.5% and 0.75%) reduced egg cholesterol levels without any adverse effect on egg weight or feed conversation ratios.…”
Section: Results and Diccussionsupporting
confidence: 89%
“…Akbarian et al. () noted that 0.50 or 0.75% ginger powder decreased cholesterol levels in the egg yolk. Also, Pavlík et al.…”
Section: Introductionmentioning
confidence: 99%
“…The hormone estrogen promotes the growth of the egg channel and increases the secretion of tubular gland, stimulates the manufacture of both yolk and white, by its work on the liver and meal and calcium deposition to be a reserve source of calcium during the period of high egg production [5]. These results were consistent with [1] who noticed the addition of the ginger powder to the meal led to a significant improvement p<0.05, estrogen hormone promotes the growth of the ovarian channel and increases the secretion of tubular glands as well as helps in the manufacture of special proteins in the egg channel such as ovalbumin, conalbumin, lysozyme, yolk protein precursor and vitellogenin, it is also possible to modulation the hormone Progesterone receptor present in cytoplasm of genetic channel cells.…”
Section: Resultssupporting
confidence: 81%
“…Recently, studies have shown that phenolic compounds (PC) have beneficial effects related to their antioxidant, anti‐inflammatory and antimicrobial activities (Akbarian et al., ; Viveros et al., ). These ingredients are found in many plants such as fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%